Conjugalidade violenta em uma mulher com neoplasia - Moura, Marines de (My University, 2021)
Domestic violence committed by an intimate partner causes several damages to the woman's life, including physical and mental health problems. Especially considering women affected by cancer, this violence acquires greater relevance. This research aimed to: discuss possible relationships of violent marital dynamics in a woman with cancer. For this, scientific knowledge produced on gender violence against women, violent marital dynamics and neoplasia was gathered in order to carry out an analysis correlating the consequences of the nature of this violence in a woman with neoplastic condition. This is a qualitative research, with an exploratory basis. For the development of this work, the records of the interviews of a participant of an operative group, which is linked to an institutional research, were used as a source. The transcribed interviews were made available by the researcher and also the supervisor of this study. For data collection, a table of contents was created. From this, the reading of the contents began and, later, their categorization, from the grouping of themes manifested in the participant's reports. The analysis framework was content analysis. The main results presented pointed to two discussion categories: In the first category, called characteristics of the couple's relational dynamics, a contextualization and characterization of the participant's relationship with her current partner was presented, consisting of twelve sections. In the second category, neoplasia in the context of violent marital dynamics, the experiences of conjugality in the face of the participant's illness were addressed, discussed in five sections. From this, the final considerations of this study emphasize that the violence practiced by an intimate partner represents suffering to the participant with several damages to her life and health. However, there are aspects such as the naturalization of violence and the idealization of the relationship and the partner that need to be considered in this scenario. Especially in relation to the process of illness and conjugality, the lack of support from the aggressor partner in coping with the disease stands out, as well as the repercussions of frustration and dissatisfaction with the quality of the relationship, as well as damage to the woman's self-esteem and self-image. [resumo fornecido pelo autor]
A violência conjugal praticada por parceiro íntimo provoca vários danos na vida da mulher, entre eles problemas na saúde física e mental. Considerando especialmente a mulher acometida por câncer, essa violência adquire maior relevância. Esta pesquisa teve como objetivo: discutir possíveis relações da dinâmica conjugal violenta em uma mulher com neoplasia. Para isso, foi reunido conhecimentos científicos produzidos sobre a violência de gênero contra a mulher, dinâmica conjugal violenta e neoplasia, a fim de realizar uma análise correlacionando as consequências da natureza dessa violência em uma mulher com quadro neoplásico. Trata-se de uma pesquisa de caráter qualitativa, de base exploratória. Para o desenvolvimento deste trabalho foi utilizado como fonte os registros das entrevistas de uma participante de um grupo operativo, o qual está vinculado a uma pesquisa institucional. As entrevistas transcritas foram disponibilizadas pela pesquisadora e, também, orientadora deste estudo. Para a coleta dos dados, foi realizada uma Tabela de Recorte de conteúdos. A partir dessa, iniciaram as leituras dos conteúdos e, posteriormente, a categorização dos mesmos, a partir do agrupamento de temáticas manifestadas nos relatos da participante. O referencial de análise foi a análise de conteúdo. Os principais resultados apresentados apontaram para duas categorias de discussão: Na primeira categoria, denominada características da dinâmica relacional do casal, foi apresentado uma contextualização e caracterização do relacionamento da participante com seu atual companheiro, composta por doze recortes. Na segunda categoria, neoplasia no contexto da dinâmica conjugal violenta, foi abordado as vivências da conjugalidade diante da doença da participante, discutidas através de cinco recortes. A partir disso, as considerações finais deste estudo enfatizam que a violência praticada por parceiro íntimo representa sofrimento à participante com vários prejuízos para sua vida e saúde. No entanto, há aspectos como a naturalização da violência e a idealização da relação e do parceiro, que são necessários de serem considerados nesse cenário. Especialmente em relação ao processo de adoecimento e conjugalidade, destaca-se a falta de apoio do parceiro agressor no enfrentamento da doença, bem como as repercussões, desta, de frustração e insatisfação da qualidade do relacionamento, bem como prejuízos à autoestima e autoimagem da mulher. [resumo fornecido pelo autor]
Keywords: Psicologia; Discriminação de sexo contra as mulheres; Violência contra as mulheres; Violência conjugal; Câncer